Ancient polymorphism and functional variation in the primate MHC-DQA1 5′ cis-regulatory region - Loisel, Dagan A. (National Academy of Sciences, 2006)
Precise regulation of MHC gene expression is critical to vertebrate immune surveillance and response. Polymorphisms in the 5′ proximal promoter region of the human class II gene HLA-DQA1 have been shown to influence its transcriptional regulation and may contribute to the pathogenesis of autoimmune diseases. We investigated the evolutionary history of this cis-regulatory region by sequencing the DQA1 5′ proximal promoter region in eight nonhuman primate species. We observed unexpectedly high levels of sequence variation and multiple strong signatures of balancing selection in this region. Specifically, the considerable DQA1 promoter region diversity was characterized by abundant shared (or trans-species) polymorphism and a pronounced lack of fixed differences between species. The majority of transcription factor binding sites in the DQA1 promoter region were polymorphic within species, and these binding site polymorphisms were commonly shared among multiple species despite evidence for negative selection eliminating a significant fraction of binding site mutations. We assessed the functional consequences of intraspecific promoter region diversity using a cell line-based reporter assay and detected significant differences among baboon DQA1 promoter haplotypes in their ability to drive transcription in vitro. The functional differentiation of baboon promoter haplotypes, together with the significant deviations from neutral sequence evolution, suggests a role for balancing selection in the evolution of DQA1 transcriptional regulation in primates.